Import of proteins into mitochondria: precursor forms of the extramitochondrially made F1-ATPase subunits in yeast. - Maccecchini, M L (1979)
The mitochondrial F1-ATPase consists of five nonidentical subunits that are synthesized outside the mitochondria and imported across both mitochondrial membranes to the matrix side of the inner membrane. In order to study the mechanism of this import, we synthesized the F1-ATPase subunits of yeast either in vitro (in a reticulocyte lysate programmed with yeast RNA) or in vivo (in pulsed and pulsed-chased yeast spheroplasts). Both in vitro and in vivo, each of the three largest ATPase subunits was synthesized as a larger precursor. When the precursors that had been synthesized in vitro were incubated with isolated yeast mitochondria, they were converted to "mature" subunits that were no longer susceptible to externally added proteases. The uptake of the subunit into the mitochondria was thus accompanied by conversion of the precursor. Since uptake of precursors into mitochondria was independent of protein synthesis and since the precursors could also be detected in vivo, the transfer of proteins from the cytosol across both mitochondrial membranes does not occur by vectorial translation. Instead, the proteins destined for import are first made outside the mitochondria as precursors and only subsequently transported into the mitochondria. This step is accompanied by proteolytic conversion of the mature subunit.